Polypyrrole/multi-walled carbon nanotube based nanocomposites as electrode materials for supercapacitors applications - Ng, Daniel Hoe Zhiat. (2012)
Supercapacitor store considerable amount of energy compared to conventional capacitors in addition to boost power output. According to previous studies, it was found that supercapacitors made of electrode material such as polypyrrole/acid-functionalized single-walled carbon nanotubes composites have shown great improvement in specific capacitances and specific energy. Hence this report was written about the electrochemical and thermal performance of polypyrrole/acid-functionalized multi-walled carbon nanotubes composite electrode material in comparison with pristine polypyrrole and polypyrrole /MWCNTs composite.